"E-UMKM" Mobile Application to Increase Productivity and Competitiveness of MSMEs in the Digital Era: Evaluation and Implementation in the Digital Era - Fajar Indra Kusuma; Izma Fatima; Laras Andita Yuningtyas; Dita Octaviani (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2024)
Digital technology continues to develop rapidly and influence the MSME sector. The development of digital applications for MSMEs, such as BukuKas and Majoo, has helped business people manage their business more efficiently, from financial management to digital marketing. These applications simplify administrative tasks, expand market access, and increase competitiveness. This research uses the 4-D model in development application, involving media, content and MSME practitioner expert validators to assess the feasibility of the application. The research instrument is a questionnaire with a Likert scale, assessed by Media, Content and MSME Practitioner experts with results showing the application is very suitable for use. This application provides account verification features, MSME profiles, MSME news updates, and online seminars. The feasibility assessment shows very good results from media experts being 89.5%, content experts being 85.5%, and practitioner experts being 89%, making this application a potential digital tool to support the digital transformation of MSMEs. In conclusion, this application is suitable for use to increase productivity and the competitiveness of MSMEs in the digital era.